JOB READINESS OF VOCATIONAL HIGH SCHOOL STUDENTS INFLUENCED BY FIELDWORK PRACTICES, WORK MOTIVATION AND SOFT SKILL MASTERY - Fahriati, Ishar; Yohana, Corry; Faslah, Roni (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to determine the influence of fieldwork practice, work motivation, and soft skills on job readiness. The population in this study consists of 248 twelfth-grade students from SMKN 6 Jakarta. The sample selection was determined using Slovin’s formula with a 5% margin of error, resulting in a sample of 153 respondents. This research employs quantitative data analysis techniques using a survey method, where data was collected through a questionnaire formatted in Google Forms. The findings reveal that fieldwork practice has a significant positive impact on job readiness. Additionally, work motivation also has a significant positive influence on job readiness. Similarly, soft skills have a significant positive effect on job readiness. Overall, fieldwork practice, work motivation, and soft skills collectively have a significant positive impact on job readiness. The coefficient of determination indicates that these three variables contribute 44.7% to job readiness, while the remaining percentage is influenced by other factors not examined in this study.